Comparative Analysis of Decision Tree and Random Forest Algorithms for Diabetes Prediction - Fadhlullah, Aufar Faiq; Widiyaningtyas, Triyanna (Universitas Muhammadiyah Mataram, 2024)
Diabetes Mellitus is a long-term medical disorder marked by high blood glucose levels that raise the risk of early mortality and organ failure. It has become an increasing global health problem, so making an accurate and timely diagnosis is urgently necessary. This study aims to diagnose people with diabetes mellitus by utilizing prediction techniques in data mining using experimental research. The prediction stage for diagnosing diabetes consists of four stages: dataset collection, data pre-processing, data processing, and evaluation. Data was obtained from Electronic Health Records (EHRs), namely the public